2007
DOI: 10.5194/fr-10-38-2007
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the cervical skeleton posture of <i>Brachiosaurus brancai</i> Janensch, 1914 by an analysis of the intervertebral stress along the neck and a comparison with the results of different approaches

Abstract: The neck posture of Brachiosaurus brancai Janensch, 1914 is reanalysed by employing the Preuschoft method to deduce the pattern of stress in the joints between the vertebral centra along the neck. The cogency of different methods for reconstructing the posture of a long neck, especially the Preuschoft method and approaches that are based on optimal articulation of the neck vertebrae, is discussed critically. The results corroborate the reliability of the Preuschoft method whereas the analyses of recent vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 11 publications
7
59
0
Order By: Relevance
“…Raising the head above the shoulders at rest and during locomotion is a common feature of low feeding extant terrestrial vertebrates with long necks, like ostriches and camels. Usually, the neck is kept in a higher position during rest than during locomotion (Dzemski, 2005;Christian and Dzemski, 2007). For sauropods, keeping their long neck always in a very low position, as proposed by Stevens and Parish (1999), is unlikely due to ecological reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raising the head above the shoulders at rest and during locomotion is a common feature of low feeding extant terrestrial vertebrates with long necks, like ostriches and camels. Usually, the neck is kept in a higher position during rest than during locomotion (Dzemski, 2005;Christian and Dzemski, 2007). For sauropods, keeping their long neck always in a very low position, as proposed by Stevens and Parish (1999), is unlikely due to ecological reasons.…”
Section: Discussionmentioning
confidence: 99%
“…According to Stevens and Parish (1999), in the habitual neck postures of vertebrates with long necks the facets of the prezygapophyses and the postzygapophyses are aligned and centered. Detailed studies by Christian and Dzemski (2007), however, revealed that such ''best fit'' or zygapophyseal alignment postures can deviate considerably from the habitual neck postures at rest, but can resemble the neck postures that are employed during locomotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In seeking to determine the neck posture of sauropod dinosaurs, researchers must interpret anatomy from an incomplete fossil record. In previous reconstructions of the sauropod body plan, researchers have proposed an upward sloping curve for the neck (see Christian & Dzemski, 2007); others have posited a straight, horizontal or downward curving sloping neck (Stevens & Parrish, 1999). Yet others (Taylor et al, 2009) have argued that sauropods held their necks extended with their heads flexed such that the mid-cervical region was near vertical.…”
Section: Abductive Reasoningmentioning
confidence: 99%
“…The amount of overlap that remains between the zygapophyses during maximum flexion is hotly debated in the literature (e.g., Parrish 1999, 2005a, b;Christian and Dzemski 2007;Taylor et al 2009). In light of the research of Christian and Dzemski (2007) and Taylor et al (2009) it seems plausible that zygapophysal articulations especially in the neck can move so that overlap of significantly less than 50% occurs.…”
Section: Range Of Motion Analysesmentioning
confidence: 99%